Age-related differences in the association between financial hardship and weight change during the COVID-19 pandemic - Izabelle Mendez; Paula D. Strassle; Stephanie Ponce; Randy Le; Anita L. Stewart; Anna M. Nápoles (Heliyon, 2024)
Objective: To examine the association of financial hardship with weight changes in the US during the COVID-19 pandemic. Methods: We used data from the COVID-19's Unequal Racial Burden survey, a nationally representative, cross-sectional, online survey of diverse adults living in the US, 12/2020-2/2021. This study included 1000 Asian, Black, Latino (half Spanish-speaking), and White adults and 500 American Indian or Alaska Native, Native Hawaiian or Pacific Islander, and multiracial adults (5500 total). Age-specific (18–39, 40–59, ≥60) associations between financial hardship domains and weight change were estimated using multinomial logistic regression, adjusted for demographic and health characteristics. Results: Financial hardship during the COVID-19 pandemic was prevalent across all age groups (18–39: 76.2 %; 40–59: 75.6 %; ≥60: 50.6 %). Among adults aged 18–39 and ≥ 60 years old, food insecurity was significantly associated with weight loss (18–39: aOR = 1.42, 95 % CI = 1.04, 1.95; ≥60: aOR = 3.67, 95 % CI = 1.50, 8.98). Among all age groups, unmet healthcare expenses was also associated with weight loss (18–39: aOR = 1.31, 95 % CI = 1.01, 1.70; 40–59: aOR = 1.49, 95 % CI = 1.06, 2.08; ≥60: aOR = 1.73, 95 % CI = 1.03, 2.91). Among adults aged 18–39 and ≥ 60 years old, lost income was significantly associated with weight gain (18–39: aOR = 1.36, 95 % CI = 1.09–1.69; ≥60: aOR = 1.46, 95 % CI = 1.04, 2.06), and among adults 40–59 years old, experiencing increased debt was significantly associated with weight gain (aOR = 1.50, 95 % CI = 1.13, 1.99). Conclusions: For those aged 18–39 and ≥ 60 years old experiencing financial hardship during the COVID-19 pandemic was associated with both weight loss and weight gain. Less correlation was observed among adults aged 40–59.